2012
DOI: 10.1002/ps.3339
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and herbicidal potential of substituted aurones

Abstract: It is possible that aurone derivatives, which possess structures different from those of the commercial herbicides, may become novel lead compounds for the development of herbicides against dicotyledonous weeds with further structure modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 21 publications
4
22
0
Order By: Relevance
“…When the phenyl ring B was replaced by a furan ring, the resulted molecule ( 2j ) showed a low herbicidal activity against B . campestris at 100 µg·mL −1 , which is consistent with that of 4,6‐dimethoxyaurones . In an effort to study the function of 6‐hydroxyl group, modification of 6‐hydroxyl group by alkylation with 1‐chloroacetone was carried out.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…When the phenyl ring B was replaced by a furan ring, the resulted molecule ( 2j ) showed a low herbicidal activity against B . campestris at 100 µg·mL −1 , which is consistent with that of 4,6‐dimethoxyaurones . In an effort to study the function of 6‐hydroxyl group, modification of 6‐hydroxyl group by alkylation with 1‐chloroacetone was carried out.…”
Section: Resultssupporting
confidence: 71%
“…crus‐galli ). The results revealed that 6‐hydroxyaurones possessed the same selectivity as 4,6‐dihydroxyaurones, but showed slightly lower herbicidal activity than the latter .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Aurones, (Z)-2-benzylidenebenzofuran-3-(2H)-ones ( Figure 1c), constitute a less studied subclass of flavonoids although they are isosteres of flavones 5,6 . However, they have attracted attention with promising biological potential such as anti-microbial 7 , anti-cancer 8 , anti-leishmanial [9][10][11] , anti-histaminic 12 , antiinflammatory 13 , antioxidant 14 , insect anti-feedant 15 , herbicidal 16 , anti-HIV 17,18 , anti-HCV (hepatis C virus) 19,20 , anti-malarial 21,22 , ChE inhibitory 23,24 , MAO inhibitory 25 activities in the specified studies. The observed biological potential is thought to be due to the similarity of adenine of ATP and the flavonoids, consequently inhibition of the activity of ATP-dependent enzymes and proteins, which is essential for the function of enzymes and receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Aurones (2‐benzylidenebenzofuran‐3(2 H )‐ones), as isomers of flavones, are naturally occurring yellow pigments from plants. They demonstrate a great diversity of biological activities, including antimicrobial , anticancer , antiviral , antifungal , and herbicidal activities. It was also reported that aurone derivatives could serve as fluorescent probes to detect CN − and biomacromolecules .…”
Section: Introductionmentioning
confidence: 99%